2019
DOI: 10.4103/ijt.ijt_18_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of efficacy of topical mometasone with calcipotriol versus mometasone alone in the treatment of alopecia areata

Abstract: Background: Alopecia areata is one of the common causes of nonscarring hair loss with autoimmune etiology. This study was designed to evaluate any added benefit of topical calcipotriol when combined with topical mometasone in the treatment of alopecia areata. To the best of our knowledge, no such study has been conducted in the past. Materials and Methods: It was a comparative analytical study done over 100 patients of clinically diagnosed alopecia areata. Group A patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A meta-analysis of available RCTs showed a significant improvement in SLEDAI scores, fatigue (when assessed in two studies), and serum C3; in contrast, serum C4 and anti-dsDNA changes were insignificant ( 359 ). In AA, application of topical calcipotriol, a vitamin D analogue, has been shown to be an effective treatment in most mild-to-moderate patients ( 298 , 360 , 361 ), particularly those with deficiencies ( 362 ). However, these studies in AA often lack placebo arms and randomized, clinical trials with larger groups of patients are greatly needed.…”
Section: Perspectives: Therapeutic Interventionsmentioning
confidence: 99%
“…A meta-analysis of available RCTs showed a significant improvement in SLEDAI scores, fatigue (when assessed in two studies), and serum C3; in contrast, serum C4 and anti-dsDNA changes were insignificant ( 359 ). In AA, application of topical calcipotriol, a vitamin D analogue, has been shown to be an effective treatment in most mild-to-moderate patients ( 298 , 360 , 361 ), particularly those with deficiencies ( 362 ). However, these studies in AA often lack placebo arms and randomized, clinical trials with larger groups of patients are greatly needed.…”
Section: Perspectives: Therapeutic Interventionsmentioning
confidence: 99%
“…Narang et al (62) found that patients with alopecia areata were treated with 0.005% calcitriol lotion for 3 months with significant improvement in disease severity. Alam et al (63) also found that external use of 0.005% calcipotriol ointment combined with external use of 0.1% mometasone cream had better efficacy in the treatment of alopecia areata than external use of mometasone alone. However, studies such as double-blind clinical trials with larger samples are needed to further demonstrate the efficacy of vitamin D analogs in combination with other traditional therapies in patients with alopecia areata.…”
Section: The Application Of Antioxidant In the Treatment Of Alopecia ...mentioning
confidence: 99%
“…In another study by Çerman and co-workers [131], 48 patients with mild and moderate AA who failed topical steroids, displayed a total hair regrowth of 27.1% (13/36) at 12 weeks after undergoing calcipotriol monotherapy. Successful treatments have been reported combining calcipotriol with potent corticosteroids such as mometasone, and clobetasol compared to their monotherapeutic efforts [132,133].…”
Section: Alopecia Areatamentioning
confidence: 99%